A Comprehensive Analysis of Thermal Heat Dissipation for Lithium-Ion Battery Packs - Xuguang Zhang; Hexiang Zhang; Amjad Almansour; Mrityunjay Singh; James D. Kiser; Hengling Zhu; Michael C. Halbig; Yi Zheng (Energies)
Effective thermal management is essential for the safe and efficient operation of lithium-ion battery packs, particularly in compact, airflow-sensitive applications such as drones. This study presents a comprehensive thermal analysis of a 16-cell lithium-ion battery pack by exploring seven geometric configurations under airflow speeds ranging from 0 to 15 m/s and integrating nano-carbon-based phase change materials (PCMs) to enhance heat dissipation. A Computational Fluid Dynamics (CFD) approach was employed using Ansys Discovery and Workbench 2024 R1 to simulate airflow and heat transfer processes with high spatial resolution. Using high-fidelity 3D simulations, we found that the trapezoidal wide-base configuration, combined with a 5-inlet and 1-outlet airflow design, achieved the most balanced cooling performance across all speed regimes. This configuration maintained battery temperatures within the optimal operating range (∼45 °C) in both low- and high-speed airflow conditions, with a maximum temperature reduction of up to 8.3 °C compared to the standard square configuration. Additionally, PCM integration extended the thermal regulation duration to approximately 12.5 min, effectively buffering thermal spikes during peak loads. These findings underscore the critical role of CFD-driven geometric optimization and advanced material integration in designing high-efficiency, compact cooling systems for energy-dense battery applications in drones and portable electronics.